LINGVOCULTURAL INTERFERENCE IN LEARNING THE ENGLISH LANGUAGE - Naimova D. K. (Journals Park Publishing, 2024)
This article deals with the influence of the native language on learning a foreign language and overcoming its interfering aspects. Based on the analysis of domestic and foreign methodological literature, the author identifies the following types of linguocultural interference: phonological, grammatical, lexical, syntactic and sociocultural. To overcome interference, a special set of exercises is required to ensure maximum weakening of the effects of the identified types of interference.
Keywords: interlinguistic, communicative competence, lingvoculture, target language.